Study on the threshold interfacial shear stiffness of simply supported composite girders. (1st October 2022) - Liang, Chen; Liu, Yuqing; Chen, Shenggen; Lu, Chi
Highlights: The concept of threshold stiffness is proposed for composite bridge girders. The equations for threshold stiffness in deflection are derived and verified. Any two-step distribution of interfacial stiffness can be considered. The effects of geometries and connector arrangement are discussed. Abstract: The strength-based categorization of composite action, which is adopted by most current specifications, may not be applicable in the deflection calculation of bridge girders. Therefore, this paper defines the threshold stiffness as the minimum required shear stiffness at the steel–concrete interface for a composite girder to be regarded as full shear interaction in deflection calculation. To determine the threshold stiffness of simply supported composite girder with a two-step arrangement of shear connectors, based on the elastic theoretical model of composite girders considering slip, two lower-bound scenarios were analyzed, and the relationship between the midspan deflection and the interfacial stiffness was first derived. Next, by controlling the deflection differences between full shear interaction and proposed scenarios to be below 5%, the equations of the threshold stiffness were derived under concentrated load, uniformly distributed load and differential thermal effects or shrinkage. The equations were then verified with a large number of finite element models. The effects of span-to-web height ratios, concrete-to-steel area ratios, and connector arrangements were analyzed within the common design range. The results show that the threshold stiffness equations are in good agreement with the finite element results. For the investigated load cases, the threshold stiffness is the highest when subjected to a concentrated load at midspan. The threshold stiffness decreases with increases in the span-to-web height ratio and the web height, and increases with the width of the concrete slab and the flange thickness, among which the span-to-web height ratio has the most significant effect. The main feature of the proposed equations is that they can consider any uniform or two-step distribution of shear connectors, which cover most cases in simply supported composite bridge girders.